Ankle synovial chondromatosis in anterior and posterior compartments. A Case report. - Zmerly, Hassan; Mauela, Moscato; Akkawi, Ibrahim (Acta Biomedica Atenei Parmensis, 2020)
Synovial chondromatosis is a rare benign disease, the aetiology of which is not clear. It can arise in the synovial membrane of joints, tendon sheaths, or bursae. Synovial chondromatosis is characterized by multiple loose bodies that can grow and cause symptoms such as pain, swelling and a limited range of motion. It can also result in joint damage. We describe the case of a 48-year-old male dancer with ankle synovial chondromatosis. Diagnosis by radiograph and MRI showed multiple lesions in anterior and posterior ankle compartments. The patient was successfully treated with arthroscopic removal of all loose bodies and partial synoviectomy. Clinical follow-ups at one, four and 12 months and again at 10 years, showed the ankle had a full range of motion without pain or swelling. Post-operative radiographs at one month and at 10 years showed no lesions. Synovial chondromatosis is a benign condition with several loose bodies that must be removed to relieve symptoms and avoid future joint damage. The ankle is a rare location for chondromatosis and arthroscopic removal is the treatment of choice with good results.